The Mycetoma Research Center, University of Khartoum, Sudan's experience in community engagement initiatives spans 3 decades. - Ahmed Hassan Fahal; Eiman Siddig Ahmed; Ahmed Hussein Mahmoud; Ali Awadella Saaed (Public Library of Science (PLoS), 2024)
Mycetoma profoundly affects marginalised communities, especially in impoverished and remote areas with limited access to healthcare. This chronic and debilitating inflammatory disease highlights the typical issues of neglected tropical diseases (NTDs), such as insufficient attention, funding, and resources, which perpetuate neglect and suffering. Patients often delay seeking medical help, leading to advanced disease stages, severe complications, and lasting disabilities. The lack of medical infrastructure and skilled healthcare professionals worsens the situation, causing delays in diagnosis and inadequate treatment. Engaging affected communities in tailored interventions is essential to tackle these challenges, promote collaboration, raise awareness, and mobilise resources to improve healthcare access and enhance diagnostic and treatment capabilities. Since 1991, the Mycetoma Research Center (MRC) at the University of Khartoum, Sudan, has led community engagement initiatives aimed at improving the quality of life for mycetoma-affected individuals through education, advocacy, and local collaboration. In this communication, the MRC shares its extensive experience in community engagement to benefit mycetoma-affected communities.